Differential Expression Profiles in the Midgut of Triatoma infestans Infected with Trypanosoma cruzi - Buarque, Diego S.; Braz, Glória R. C.; Martins, Rafael M.; Tanaka-Azevedo, Anita M.; Gomes, Cícera M.; Oliveira, Felipe A. A.; Schenkman, Sergio; Tanaka, Aparecida S. (PLOS ONE, 2013)
Chagas disease, or American trypanosomiasis, is a parasitic disease caused by the protozoan Trypanosoma cruzi and is transmitted by insects from the Triatominae subfamily. To identify components involved in the protozoan-vector relationship, we constructed and analyzed cDNA libraries from RNA isolated from the midguts of uninfected and T. cruzi-infected Triatoma infestans, which are major vectors of Chagas disease. We generated approximately 440 high-quality Expressed Sequence Tags (ESTs) from each T. infestans midgut cDNA library. The sequences were grouped in 380 clusters, representing an average length of 664.78 base pairs (bp). Many clusters were not classified functionally, representing unknown transcripts. Several transcripts involved in different processes (e.g., detoxification) showed differential expression in response to T. cruzi infection. Lysozyme, cathepsin D, a nitrophorin-like protein and a putative 14 kDa protein were significantly upregulated upon infection, whereas thioredoxin reductase was downregulated. In addition, we identified several transcripts related to metabolic processes or immunity with unchanged expressions, including infestin, lipocalins and defensins. We also detected ESTs encoding juvenile hormone binding protein (JHBP), which seems to be involved in insect development and could be a target in control strategies for the vector. This work demonstrates differential gene expression upon T. cruzi infection in the midgut of T. infestans. These data expand the current knowledge regarding vector-parasite interactions for Chagas disease.